Pembuatan Kompos Daun Kering Dari Sampah Lingkungan Dusun Pal 6 Desa Karang Sari, Kecamatan Jati Agung - Emantis Rosa; Yulianti; Selvi Marcelia; Linda Septiani (CV. Multi Kreasi Media, 2025)
Compost is a material produced from the decomposition process of organic matter, such as wet or dry, husk, garbage and so on. The benefits of compost, apart from reducing organic waste by turning it into useful materials, can improve soil quality and increase plant productivity.. The purpose of this community service activity is to provide knowledge, understanding and skills in making compost fertilizer from dry leaves found in the environment to residents in Dusun Pal 6, Desa Karang Sari, Kecamatan Jati Agung. The results of the assessment show that there is an increase in knowledge and understanding of the materials provided with an initial percentage of 52.0% increased by 77.05% with an average increase of 28.3%, the highest increase range is 41% and the lowest is 16%